The Antecedents and Outcomes of Brand Love in Malaysian Context - Chin, Shih Yuan (2013)
This research explores the antecedents and outcome of brand love. Consumer-brand relationship constructs, brand trust, brand credibility and brand equity may influence consumers' brand love. Brand love in turn may have positive impact towards brand commitment. Quantitative survey research is employed to test the hypotheses involving brand love and brand commitment. Results show that brand trust, brand experience, brand credibility and brand equity relates positively towards brand love. Consumers love towards brand has direct effect on brand commitment. Result also suggests that there is positive relationship between brand equity and brand credibility towards brand commitment.